Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2024
DOI: 10.1093/geroni/igae010
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Older Person’s Grant Expansion on Hypertension Among Older Men in Rural South Africa: Findings From the HAALSI Cohort

Haeyoon Chang,
Janet Jock,
Molly S Rosenberg
et al.

Abstract: Background and Objectives Hypertension is a major modifiable contributor to disease burden in sub-Saharan Africa. We exploited an expansion to age eligibility for men in South Africa’s non-contributory public pension to assess the impact of pension eligibility on hypertension in a rural, low-income South African setting. Research Design and Methods Data were from 1,247 men aged ≥60 in the population-representative Health and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Beyond individual psychological factors that contribute to retirement outcomes, country-level policies can also influence this transition. Data from over 1,000 older men from a cohort study in South Africa examined some potential unintended consequences of recent expansions in pension eligibility on hypertension ( Chang et al, 2024 ). The study found that while the expanded pension eligibility will likely have long-term positive effects, there was a small short-term negative effect on hypertension among older men.…”
Section: Adapting To Changing Timesmentioning
confidence: 99%
“…Beyond individual psychological factors that contribute to retirement outcomes, country-level policies can also influence this transition. Data from over 1,000 older men from a cohort study in South Africa examined some potential unintended consequences of recent expansions in pension eligibility on hypertension ( Chang et al, 2024 ). The study found that while the expanded pension eligibility will likely have long-term positive effects, there was a small short-term negative effect on hypertension among older men.…”
Section: Adapting To Changing Timesmentioning
confidence: 99%